2012
DOI: 10.1002/ajpa.22179
|View full text |Cite
|
Sign up to set email alerts
|

Victims and survivors: Stable isotopes used to identify migrants from the Great Irish Famine to 19th century London

Abstract: Historical evidence documents mass migration from Ireland to London during the period of the Great Irish Famine of 1845-52. The rural Irish were reliant on a restricted diet based on potatoes but maize, a C(4) plant, was imported from the United States of America in 1846-47 to mitigate against Famine. In London, Irish migrants joined a population with a more varied diet. To investigate and characterize their diet, carbon and nitrogen isotope ratios were obtained from bone collagen of 119 and hair keratin of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 43 publications
6
91
0
Order By: Relevance
“…In total, the Famine‐period mass burial ground at the Kilkenny Union Workhouse contained the remains of a minimum of 970 individuals (545 nonadults and 425 adults) (Geber, 2015). Isotope analysis of a subsample ( n = 13) have revealed the population group subsisted on a more or less exclusively vegetarian diet (Beaumont et al, 2013; Beaumont & Montgomery, 2016), which conforms to nineteenth‐century historical accounts of the diet of the poor in this part of Ireland (Tighe, 1802). Preliminary analysis of dental calculus (Geber, 2016) has also revealed that, although potato and dairy products were largely consumed, the diet was supplemented with other vegetables (probably opportunistically and possibly related to relief food rations during the Famine period).…”
Section: Methodsmentioning
confidence: 61%
“…In total, the Famine‐period mass burial ground at the Kilkenny Union Workhouse contained the remains of a minimum of 970 individuals (545 nonadults and 425 adults) (Geber, 2015). Isotope analysis of a subsample ( n = 13) have revealed the population group subsisted on a more or less exclusively vegetarian diet (Beaumont et al, 2013; Beaumont & Montgomery, 2016), which conforms to nineteenth‐century historical accounts of the diet of the poor in this part of Ireland (Tighe, 1802). Preliminary analysis of dental calculus (Geber, 2016) has also revealed that, although potato and dairy products were largely consumed, the diet was supplemented with other vegetables (probably opportunistically and possibly related to relief food rations during the Famine period).…”
Section: Methodsmentioning
confidence: 61%
“…Since 2013, the number of studies has increased. Beaumont et al (2013a) investigated dietary changes during the Great Irish Famine (1845-1852 AD) and reported that weaning started and ended by 1 and 2 years of age, respectively, in possible immigrants in London. Bourbou et al (2013) reconstructed cross-sectional BWPs in Greek Byzantine populations (6th to 15th centuries AD) and found that the age at the end of weaning was <4 years.…”
Section: Applications Studied Tissuesmentioning
confidence: 99%
“…While the reconstruction of human dietary patterns using the stable isotope ratios of carbon (d 13 C) and nitrogen (d 15 N) has become widely applied in scientific archaeology, particularly in prehistory, only a small number of studies have been published on post-medieval (16th-19th c. AD) populations from Europe (Mays, 1997;Richards et al, 2006;M€ uldner and Richards, 2007;Nitsch et al, 2010Nitsch et al, , 2011Lamb et al, 2012;Roberts et al, 2012;Beaumont et al, 2013;Salesse et al, 2013). This is unfortunate since, unlike most documentary sources, skeletal remains have the ability to act as an important and unbiased source of paleodietary information which is specific to a site or population.…”
Section: Diet Reconstruction Using Stable Isotope Ratiosmentioning
confidence: 99%
“…Post-medieval datasets from England date mostly to the late 18th and 19th century, somewhat later than the Aalst samples (16th-18th c. AD). Of these, humans from London and York especially demonstrate isotopically very similar diets to the Aalst population, including the consumption of marine fish in measurable quantities (M€ uldner and Richards, 2007;Nitsch et al, 2010;Beaumont et al, 2013). In other populations, a marine contribution to the diet is less clear, although possibly obscured by dietary breadth and, in some cases, the consumption of C 4 foods (Richards et al, 2006;Roberts et al, 2012).…”
Section: General Trendsmentioning
confidence: 99%